2022
DOI: 10.1038/s42003-022-03594-4
|View full text |Cite
|
Sign up to set email alerts
|

KHSRP loss increases neuronal growth and synaptic transmission and alters memory consolidation through RNA stabilization

Abstract: The KH-type splicing regulatory protein (KHSRP) is an RNA-binding protein linked to decay of mRNAs with AU-rich elements. KHSRP was previously shown to destabilize Gap43 mRNA and decrease neurite growth in cultured embryonic neurons. Here, we have tested functions of KHSRP in vivo. We find upregulation of 1460 mRNAs in neocortex of adult Khsrp−/− mice, of which 527 bind to KHSRP with high specificity. These KHSRP targets are involved in pathways for neuronal morphology, axon guidance, neurotransmission and lon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 89 publications
0
17
0
Order By: Relevance
“…5 F), including ELAVL1, which reduces neuronal cytoplasmic mRNA; CUGBP Elav-like family member 4 (CELF4); and KHSRP ( Supplemental Fig. S5I ; Engel et al 2022 ; Olguin et al 2022 ; Patel et al 2022 ). KHSRP and CELF4 regulate mRNA abundance in axons and dendrites ( Snee et al 2002 ), whereas pumilio RNA binding family member 2 (PUM2) shapes the transcriptome in developing axons by retaining mRNAs in the cell body ( Martínez et al 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 F), including ELAVL1, which reduces neuronal cytoplasmic mRNA; CUGBP Elav-like family member 4 (CELF4); and KHSRP ( Supplemental Fig. S5I ; Engel et al 2022 ; Olguin et al 2022 ; Patel et al 2022 ). KHSRP and CELF4 regulate mRNA abundance in axons and dendrites ( Snee et al 2002 ), whereas pumilio RNA binding family member 2 (PUM2) shapes the transcriptome in developing axons by retaining mRNAs in the cell body ( Martínez et al 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…The ratio between the genes’ abundance in the axons and in the cell body is often used to quantify mRNA axonal localization ( Martínez et al 2019 ; Olguin et al 2022 ); however, this metric correlates with the mRNA abundance in the cell body and the transcript length ( Supplemental Fig. 3C,D ).…”
Section: Methodsmentioning
confidence: 99%
“…KHRSP has been shown to be highly expressed in the brain tissue. It plays an important role in neuronal development by regulating axonal branching and elongation, while its deficits were linked to impaired neuronal development [109,110].…”
Section: Ribosomal Protein Involvement In Neural Differentiationmentioning
confidence: 99%
“…Recently published research on synaptic molecular mechanisms of memory consolidation revealed new insights into the role of KH-type splicing regulatory protein (KHSRP) [ 31 ]. Specifically, the loss of KHSRP was found to increase neuronal growth and synaptic transmission while also altering memory consolidation through RNA stabilization [ 31 ].…”
Section: Mainmentioning
confidence: 99%